Comparison of the thermal characteristics and temperature profile of the ground in Cyprus with other Mediterranean countries - Florides, Georgios A.; Pouloupatis, Panayiotis; Kalogirou, Soteris A.; Messaritis, Vassilios; Panayides, Ioannis; Zomeni, Zomenia; Partasides, George; Lizides, Andreas; Sophocleous, Eleni; Koutsoumpas, Kostas (My University, 2010)
The purpose of this study is to record and compare the ground temperatures and other thermal characteristics of the ground at eight representative sites in Cyprus with other studies both in the island and the nearby Mediterranean countries. Paul Morgan in the 1970s measured the geothermal gradient in 33 boreholes in Cyprus. Since then, the thermal behaviour of the ground has not been sufficiently studied and recorded, especially in inhabited areas, resulting in limited information for the design of ground heat exchangers and its effect on the efficiency of Ground Coupled Heat Pumps (GCHPs). As simulation studies indicate the ground temperature is one of the main system parameters that affect the performance of GCHPs. Measurements carried out on the representative locations in Cyprus show that the surface zone reaches a depth of 0.5m. The shallow zone penetrates to 7-8 m and there after the deep zone follows. Also the temperature of the ground at the deep zone has a range between 18-23 °C and is usually higher than that of the ambient air during the cold months of the year and lower during the warm months, showing suitable temperatures for the efficient use of GCHPs. Ground temperatures in Cyprus are lower than those examined in Jordan and higher than the ones in Portugal.
Keywords: Geothermal; Ground temperatures; Ground thermal properties